Obstacles to scientific research in institutes of science and techniques of physical and sports activities from the viewpoint of students of adapted physical physical activity - slimani.nourdine; hobara mohamed; Ibn Abdullah Abdul Qadir (sports creativity, 2025)
The present study aimed to identify the obstacles of scientific research to the students of physical activity and the detection of the most important obstacles to scientific research that the students to the questionnaire of the obstacles of scientific research for students physical activity sports adapted, and the current study tried to answer questions about the most important obstacles to scientific research students physical activity, And the most important obstacles for students of physical activity. Field study of some institutes (Djelfa, Msila, Mostaganem). After analyzing and enriching the study variables theoretically, using a tool to measure the obstacles of scientific research for the students of physical sports activity, and making sure that the measurement tools used in the current research with the necessary psychometric characteristics were applied to the study sample of 130 students. Mathematical Activity Adaptive Activity Prepared by: Benabdallah Abdelkader- Benlarbi Oumkaltoum 2017. The analytical descriptive approach was used. After the data collection, statistical processing, presentation, analysis, interpretation and discussion based on the theoretical approach and on previous studies, The results of the current research show that the students of physical activity sports conditioned have many obstacles to scientific research between a large degree and a very large degree, according to the areas of the degree of impediments to scientific research among the proposed students, on all four axes of the questionnaire. In terms of their impact and importance to students of physical activity adapted, and can be arranged by the importance and impact of the impact of the members of the study; through the mean arithmetic of the axes of the questionnaire as follows: Obstacles related to teaching and framing - Obstacles of scientific material - Administrative obstacles - Obstacles related to students.